Investigation of magnetic flux gradients in hard superconductors - Bruk, V. V.; Eremenko, V. V.; Makedonskaya, N. I.; Shabakayeva, Yu. A.; Sirenko, V. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Analytical calculations of the transverse magnetostriction in a thin hard superconductor are presented in relation to the distributions of currents and fields within a superconducting specimen in a varied magnetic field. The approach is successfully tested on high-temperature superconductors. The flux distribution derived from magnetostriction measurements is in satisfactory agreement with that obtained from computer processing of magnetooptical images. The magnetic flux distribution below the irreversibility line of hard superconductors is derived from both original magnetization and magnetostriction measurements and image processing. Perfect consistency of the results is obtained for a family ofhigh-temperature superconductors (La2-xSrxCuO4, Bi2Sr2CaCu2Ox, YBa2Cu3O7-d).